Ludlow Castle Chapel
This was probably the first of five such round churches which were built in England under the influence of the Knights Templar. Theirs was a military monastic order, pledged to free the Church of the Holy Sepulcher in Jerusalem. The circular plan derives from the rotunda of the church built by the Emperor Constantine over the reputed tomb of Christ, and rebuilt by Crusaders in 1099.